Effectiveness of Ultrasound as a Triage Tool in Ruling out Fractures among Non-Critical Emergency Department Patients - Nik Muhamad NA,; Ganesan Murthi J,; Nik Ismail NA, (Penerbit UKM, 2015)
The popularity of ultrasound for acute diagnosis of fractures in the Emergency Department (ED) has increased over the recent years. This present study aimed to determine the sensitivity and specificity of ultrasound use for detection of fractures in a different environment, which is at the triage area of the ED. We compared the results of bedside ultrasound in detecting non-critical fractures to the current gold standard of X-rays in the triage area. The design was a single centered cross-sectional study. From August 2014 till November 2014, a total of 46 patients were recruited, creating 75 image pairs. Following consent, a bedside ultrasound was performed and subsequently compared with X-ray reporting regarding the presence or absence of fractures. SPSS analysis was used to determine the sensitivity and specificity of ultrasound in diagnosing fracture as compared to X-rays. Ultrasound had a sensitivity of 72% (95% CI, 50.6% - 87.9%) and a specificity of 80% (95%CI: 66.3 – 90%) when compared to X-rays in fracture diagnosis. The kappa analyses showed moderate inter observer agreement (0.5) between ultrasound and X-rays in diagnosing fractures. This study suggests that the use of ultrasound as a triage tool yet has unacceptable sensitivity and needs further evaluation and consideration.